Groundwater System of Khanaqin Basin in Diyala Governorate – East of Iraq - Hussein I.Z. Al-Sudani; Ahmad A. Ramadhan; Batool M. Ali M. Saeed (Tikrit Journal of Pure Science)
Land and water resources are generally depleting due to rapid increase in population, urbanization and industrialization. The demand has increased tremendously for these resources; hence optimal utilization of them is essential for sustainable development. The study area is located in Diyala Governorate in the east of Iraq covering 1920 km2. The hydrogeological investigation of the basin divided groundwater aquifers into two main units, the unconfined and confined aquifers, where geographical position, elevations, static water levels, depths, thicknesses, maximum yields as well as water sampling and pumping tests have been carried out during these investigations. Quaternary deposits, Bai Hassan and Mukdadiyah formations reflect the unconfined aquifer while confined aquifer consists of Mukdadiyah and Injana formations. The promising zone of unconfined aquifer is located around Khanaqin city within the southern part of the basin, while two promising zones of confined aquifer are located to western part of the basin and near the border within north part of the basin.